2020
DOI: 10.1088/2051-672x/ab6e23
|View full text |Cite
|
Sign up to set email alerts
|

Friction and wear resistance of polytetrafluoroethylene-based composites reinforced with ceramic particles under aqueous environment

Abstract: Polytetrafluoroethylene (PTFE) exhibits excellent potential under aqueous lubrication due to its low water absorption, low friction, and good corrosion resistance. However, its poor wear resistance limits its application. In this paper, PTFE was reinforced with different kinds of ceramic particles, and the physical properties were tested using various methods. The tribological behavior of PTFE composites sliding against a super duplex stainless steel was investigated under deionized water and seawater lubricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…with SiC, Si3N4, SiO2 (~0.5-5 µm), or h-BN (~3-5 µm) ceramic particles [15]. They found that the crystallinity of the PTFE matrix was promoted by applying these ceramic fillers.…”
Section: Lin Et Al Studied the Friction Coefficient And Wear Resistan...mentioning
confidence: 99%
See 1 more Smart Citation
“…with SiC, Si3N4, SiO2 (~0.5-5 µm), or h-BN (~3-5 µm) ceramic particles [15]. They found that the crystallinity of the PTFE matrix was promoted by applying these ceramic fillers.…”
Section: Lin Et Al Studied the Friction Coefficient And Wear Resistan...mentioning
confidence: 99%
“…Despite these advantages, PTFE suffers from poor wear resistance, which limits its application in demanding engineering and tribological systems. Various metallic or ceramic fillers (e.g., fibres, sheets, or particles) have been added to PTFE-based composites [6,[15][16][17][18][19] to modify their mechanical behaviour and enhance their abrasion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be seen from Table 3 that the most accurate value of q is obtained by minimizing the loss function in equation (15). The estimation error of q is 1.4%, which means that the degradation path fits well the true path, and handles the degradation path in different stress levels.…”
Section: Numerical Examplementioning
confidence: 87%
“…In the latter, the materials have shown a significant potential for friction and wear resistance under seawater. [12][13][14][15][16] For instance, Chen et al 18 analyzed the load effect of Si 3 N 4 -hBN ceramic/polyether ether ketone (PEEK), Carbon fiber reinforced polyether ether ketone (CF-PEEK), 17-4PH and 17-4PH coated with Cr3C2-NiCr, WC-10Co-4Cr, Cr2O3, and Al2O3-13%TiO2, respectively. These materials were also investigated by Nie et al, 17 in order to improve the abrasion resistance performance of the critical tribopairs of water hydraulic piston pump.…”
Section: Introductionmentioning
confidence: 99%
“…PTFE is well-know for its low friction, but there are considerable issues in its wear rate upon contact with hard metallic surfaces (Biswas and Vijayan, 1992), such as metal shafts. It is known that PTFE alone exhibits creep under load (Thomsen and Klit, 2011), but fillers have been used to produce PTFE composites with improved durability (Desale and Pawar, 2018; Gheisari and Polycarpou, 2019; Han et al , 2019; Lin et al , 2020; Sun et al , 2020). Recently, PTFE composites with polydopamine (PDA) showed promising results to be used as a low friction and low wear coating with excellent adhesion to metal substrates (Abe et al , 2021; Choudhury et al , 2020; Ghosh et al , 2020; Jiang et al , 2019).…”
Section: Introductionmentioning
confidence: 99%